2007
DOI: 10.1103/physrevb.76.174106
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced enhancement of ferroelectricity in multiferroicRMn2O5(R=

Abstract: Measurements of ferroelectric polarization and dielectric constant were done on RMn 2 O 5 ͑R =Tb,Dy,Ho͒ with applied hydrostatic pressures of up to 18 kbar. At ambient pressure, distinctive anomalies were observed in the temperature profile of both physical properties at critical temperatures marking the onset of long range antiferromegnetic order ͑T N1 ͒ and ferroelectricity ͑T C1 ͒, as well as at temperatures when anomalous changes in the polarization, dielectric constant, and spin wave commensurability have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…The volume of the unit cell in the LT-ICM phase is larger than that in the CM phase at ambient pressure [3], showing that the compressed lattice favors the CM phase in the RMn 2 O 5 system. In fact, electric polarization can be induced even in TbMn 2 O 5 and DyMn 2 O 5 [15] despite the difference in rare earth ions, which is indicative of the pressure-induced CM phase. Crystal as well as magnetic structure analyses under hydrostatic pressure are crucial for determining what kind of magnetic exchange interaction plays an essential role in stabilizing the LT-ICM and CM phases.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The volume of the unit cell in the LT-ICM phase is larger than that in the CM phase at ambient pressure [3], showing that the compressed lattice favors the CM phase in the RMn 2 O 5 system. In fact, electric polarization can be induced even in TbMn 2 O 5 and DyMn 2 O 5 [15] despite the difference in rare earth ions, which is indicative of the pressure-induced CM phase. Crystal as well as magnetic structure analyses under hydrostatic pressure are crucial for determining what kind of magnetic exchange interaction plays an essential role in stabilizing the LT-ICM and CM phases.…”
mentioning
confidence: 98%
“…It was recently found that a hydrostatic pressure of around 1 GPa can have a dramatic effect on the dielectric properties of Ni 3 V 2 O 8 and RMn 2 O 5 : ferroelectricity is suppressed in the former, [14] while in the latter system, ferroelectricity is restored [15] by applying pressure. In contrast to the case of an external magnetic field, where the magnetic field can directly couple to spins, pressure can tune the magnetic interaction between neighboring spins by decreasing the interatomic distance, and by changing the bond angles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This incommensurate magnetic low-temperature phase may be stabilized with respect to the commensurate phase by the application of external magnetic fields [10]. Hydrostatic pressure on the other hand has been shown to stabilize the commensurate ferroelectric phases of RMn 2 O 5 (R = Tb, Dy, Ho) [11].…”
Section: +mentioning
confidence: 99%
“…Scientific and technological interest in strongly coupled materials is principally motivated by two common characteristics of these materials. First, the strong competition among the phonon-, electron-, and spin-interactions in these materials is associated with a near degeneracy of competing ground states [15] and a consequent diverse range of phases that can be sensitively tuned with pressure, [16][17][18][19] magnetic field, [20][21][22] photon illumination, [23] and doping. [24] Second, the diverse phases of strongly coupled materials are often associated with dramatic phenomena that are both scientifically interesting and technologically important, including colossal changes of structural, electronic, and magnetic properties in response to external perturbations such as magnetic field and pressure, as well as nanometer-scale self-organization of charges (e.g., charge stripes), [25] orbitals (e.g., orbital-ordering), [26] and/or spins (e.g., magnetic polarons).…”
Section: Introductionmentioning
confidence: 99%